A comparison of Recovery Methods of Rhamnolipids Produced by Pseudomonas Aeruginosa. (2016) - Shah, Mansoor Ul Hassan; Sivapragasam, Magaret; Moniruzzaman, Muhammad; Yusup, Suzana Bt
Abstract: The high cost of downstream separation, isolation and purification of rhamnolipids are significantly high and this hampers its widespread utilization. Hence, practical and economically sound recovery methods are often sought after. This work focuses on assessing various recovery methods of rhamnolipid produced by Pseudomonas aeruginosa. These methods include that of; acid precipitation, ammonium sulphate precipitation, zinc sulphate precipitation and solvent extraction. Among these methods organic solvent extraction was found to be the best recovery technique giving the highest yield (7.5 g/L) of biosurfactant, while acid precipitation yielded the least at 3.5 g/L. Biosurfactant was supplemented with 1% crude oil (TAPIS) as the carbon source. Emulsification index (E24 ) of rhamnolipids to TAPIS was 42%.